2005
DOI: 10.1007/s10436-004-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

On user costs of risky monetary assets

Abstract: We extend the monetary-asset user-cost risk adjustment of Barnett, Liu and Jensen (1997) and their risk-adjusted Divisia monetary aggregates to the case of multiple non-monetary assets and intertemporal non-separability. Our model can generate potentially larger and more accurate CCAPM user-cost risk adjustments than those found in Barnett, Liu and Jensen (1997). We show that the risk adjustment to a monetary asset’s user cost can be measured easily by its beta. We show that any risky non-monetary asset can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Subsequently Barnett and Wu (2005) found that the explanatory power of the risk adjustment increases, if the assumption of intertemporal separability of the intertemporal utility function, T, is weakened. The reason is the same as a source of the well known equity premium puzzle, by which CCAPM under intertemporal separability under-corrects for risk.…”
Section: The Rise Of Risk Adjustment Concerns: 1984 -1993mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently Barnett and Wu (2005) found that the explanatory power of the risk adjustment increases, if the assumption of intertemporal separability of the intertemporal utility function, T, is weakened. The reason is the same as a source of the well known equity premium puzzle, by which CCAPM under intertemporal separability under-corrects for risk.…”
Section: The Rise Of Risk Adjustment Concerns: 1984 -1993mentioning
confidence: 99%
“…For example, Divisia monetary aggregates have been produced for Britain (Batchelor (1989), Drake (1992), and Belongia and Chrystal (1991)), Japan (Ishida (1984)), the Netherlands (Fase (1985)), Canada (Cockerline and Murray (1981)), Australia (Hoa (1985)), and Switzerland (Yue and Fluri (1991)), among many others. More recently, Barnett (2007) has extended the theory to multilateral aggregation over different countries with potentially different currencies, and Barnett and Shu (2005) have extended to the case of risky contemporaneous interest rates, as is particularly relevant when exchange rate risk is involved. That research was particularly focused on the needs of the European Central Bank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the under-correction produced by CCAPM results from its assumption of intertemporal blockwise strong separability of goods and services within preferences. Barnett and Wu (2005) …”
Section: Risk Adjustmentmentioning
confidence: 99%
“…1 Stochastic decision problems that include monetary or …nancial assets have been used to address a variety of topics including asset pricing [2,15,29,30,41,51], price dynamics [23,32,40,42,43], intertemporal substitution [26], money demand [21,33], currency substitution and exchange rates [6,34], optimal monetary policy [16,17,18,19,20,25], and monetary aggregation [3,4,5,46]. In each case, the usefulness of the model depends on the derivation of the stochastic Euler equations that characterize the model's solution.…”
Section: Introductionmentioning
confidence: 99%